Analysis of the biofilm formed on the surface of a glass-ionomer cement associated with different concentrations of chlorhexidine diacetate - Oliveira Becci, Ana Carolina de [UNESP]; Marti, Luana Mafra [UNESP]; Cilense Zuanon, Angela Cristina [UNESP]; Brighenti, Fernanda Lourencao [UNESP]; Palomari Spolidorio, Denise Madalena [UNESP]; Aparecida Giro, Elisa Maria [UNESP] (Mosher & Linder, Inc, 2016)
Purpose: This cross-over in situ experiment evaluated the microbial composition and quantified the total polysaccharides in the biofilm formed on the surface of a high viscosity glass-ionomer cement (GIC) mixed with chlorhexidine diacetate (CHX) in concentrations of 0.5%, 1% and 2%. GIC without CHX was used as control. Methods: The volunteers (n= 8) tested each material for a 7-day period, by using a palatal acrylic device containing four round specimens, all fabricated with the same material. An increasing order of CHX concentration and a 15-day washout period between each concentration was adopted. The biofilm formed was collected and inoculated in specific culture media and thereafter, the total microorganisms, total streptococci, Streptococcus mutans and Lactobacillus spp were counted. Total polysaccharides were quantified by using a phenol-sulfuric method. Microbiologic data were analyzed by ANOVA for repeated measures and Tukey tests, and the total polysaccharide content by Friedman and Dunn's tests. Significance level was set at 5%. Results: Microorganism counts showed statistically significant differences among groups only for Lactobacillus (P< 0.05), that were significantly higher for group GIC+CHX 2% compared with GIC and GIC+CHX 0.5%. However, the concentration of total polysaccharides in the biofilm was lower for groups containing 1% and 2% of CHX.